Analysis of Lipid Profile as a Risk Factor for Ischemic Stroke Incidence : A Systematic Review - Febriana Intan Diatri (International Medical Journal Corp. Ltd, 2026)
Background: Ischemic stroke (IS) is a leading cause of death and disability worldwide, with a complex and incompletely understood relationship with lipid parameters. Unlike coronary heart disease, the association between lipids and IS shows heterogeneity across subtypes and populations. Methods: This systematic review synthesized evidence from 80 sources, including RCT, etc. We focused on studies reporting quantitative associations between lipid profile components and IS incidence, emphasizing statistically significant positive risk factors. Results: Genetically determined LDL-C showed a modest causal effect on IS (OR 1.09, 95% CI 1.07-1.12) (1), but this was driven entirely by the large artery atherosclerosis (LAA) subtype (OR 0.75 for lower LDL-C) with null effects on cardioembolic and small vessel stroke (3). Observational data confirmed increased IS risk with elevated LDL-C (HR up to 1.74) (20) and non-HDL-C (HR 2.45) (20). HDL-C demonstrated a U-shaped relationship, with both low (HR 1.29) and very high levels (HR 1.84) increasing risk (4). Lipoprotein(a) [Lp(a)] was a significant observational risk factor (RR 1.29 per 1SD) (7) and for stroke recurrence (OR 1.69) (47), though MR evidence was weaker (1). The triglyceride-glucose (TyG) index (HR up to 2.21) (11) and atherogenic index of plasma (AIP) (HR 1.12) (10) showed strong, significant positive associations. Lp-PLA2 activity was causally linked specifically to LAA stroke (OR 3.25) (15), while oxidized LDL increased both stroke (HR 1.39) and hemorrhagic events (HR 3.61) (14). Omega-3 fatty acids DHA and DPA were protective (HR 0.80 and 0.74, respectively) (12). Discussion: The LDL-C-IS association is real but weaker than for coronary disease due to subtype heterogeneity. HDL-C is a complex marker where particle functionality supersedes total cholesterol. The discordance between observational and MR evidence for Lp(a) suggests conditional causality dependent on inflammatory and lipid milieu. Conclusion: Significant positive risk markers for IS include LDL-C, non-HDL-C, Lp(a), TyG index, AIP, Lp-PLA2 (for LAA), and oxidized LDL. Lipid management for stroke prevention must be subtype-specific and move beyond traditional LDL-C targeting.